Classify aid / Nik Nurul Aswani Nik Kamarudin ... [et al.] - Nik Kamarudin, Nik Nurul Aswani; Mohd Shaari, Siti Nabilah; Adam, Amizahanum; Abdul Raman, Suryani; Che Hasan, Haslinawati (2020)
The fundamental aspect in empowering accounting knowledge and skills is the understanding of accounting classification which will eventually help with the preparation of financial statements. Unfortunately, the common feedbacks received from accounting educators are that many students fail to see the link between the accounting classification and the financial statements. Consequently, the students choose to memorise the items to be recorded in the financial statements, instead of understanding the actual process of accounting. Therefore, we have come up with an innovation to help the accounting students to properly classify the business transactions into an asset, liability, equity, revenue and expense which will serve as a basis in the preparation and presentation of financial statements. The innovation will assist accounting students to learn the company accounts for the first time.